2016
DOI: 10.1002/adma.201603471
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Area and High‐Quality 2D Transition Metal Telluride

Abstract: Large-area and high-quality 2D transition metal tellurides are synthesized by the chemical vapor deposition method. The as-grown WTe maintains two different stacking sequences in the bilayer, where the atomic structure of the stacking boundary is revealed by scanning transmission electron microscopy. The low-temperature transport measurements reveal a novel semimetal-to-insulator transition in WTe layers and an enhanced superconductivity in few-layer MoTe .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
216
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(235 citation statements)
references
References 38 publications
(68 reference statements)
17
216
2
Order By: Relevance
“…In Figure b, Raman spectra of the CVD‐synthesized T d ‐ & 2H‐ Mo 0.32 W 0.67 Te 2.01 (blue trace) and T d ‐Mo 0.29 W 0.72 Te 1.99 (red trace) nanosheets together with the CVT‐grown T d ‐Mo 0.29 W 0.71 Te 2.0 bulk crystal (black trace) were compared to characterize their alloy features and phase identifications. For T d ‐Mo 0.29 W 0.71 Te 2.0 bulk crystal (black trace), A12 at 74.4 cm −1 (A12), 106.3 cm −1 (A13), 126.3/129.7/132.4 cm −1 (A14), 159.8 cm −1 (A17), 209.1 cm −1 (A19), and 266.4 cm −1 (A110), of which the spectral assignments consist with the earlier reports . Notably, the vibrational pattern of T d ‐Mo 0.29 W 0.72 Te 1.99 nanosheets (red trace) is similar, but has a slight blue shift, to that of T d ‐Mo 0.29 W 0.71 Te 2.0 bulk crystal (black spectra); this blue shift is attributed to the screening of long‐range Coulomb forces in the few‐layered nanosheets .…”
Section: Resultssupporting
confidence: 76%
“…In Figure b, Raman spectra of the CVD‐synthesized T d ‐ & 2H‐ Mo 0.32 W 0.67 Te 2.01 (blue trace) and T d ‐Mo 0.29 W 0.72 Te 1.99 (red trace) nanosheets together with the CVT‐grown T d ‐Mo 0.29 W 0.71 Te 2.0 bulk crystal (black trace) were compared to characterize their alloy features and phase identifications. For T d ‐Mo 0.29 W 0.71 Te 2.0 bulk crystal (black trace), A12 at 74.4 cm −1 (A12), 106.3 cm −1 (A13), 126.3/129.7/132.4 cm −1 (A14), 159.8 cm −1 (A17), 209.1 cm −1 (A19), and 266.4 cm −1 (A110), of which the spectral assignments consist with the earlier reports . Notably, the vibrational pattern of T d ‐Mo 0.29 W 0.72 Te 1.99 nanosheets (red trace) is similar, but has a slight blue shift, to that of T d ‐Mo 0.29 W 0.71 Te 2.0 bulk crystal (black spectra); this blue shift is attributed to the screening of long‐range Coulomb forces in the few‐layered nanosheets .…”
Section: Resultssupporting
confidence: 76%
“…This has important implications for the band structure of 3D MTe 2 : nearly compensated electron and hole pockets emerge, which encircle Dirac fermions with small masses; these pockets are characterized by a rotating pseudospin with consequences for circular dichroism. Recent progress in the fabrication of few-layer WTe 2 has enabled magnetoresistance measurements that support our theory of electron-hole compensation [94,95]. Our predicted dichroism has not been verified, but should now be possible to observe.…”
Section: Discussionmentioning
confidence: 67%
“…This was followed with a study on the absorption dichroism in monolayer 1T’-MoTe 2 [27]. Recently a group has shown that growth of 1T’-WTe 2 in monolayer form is possible by CVD [28] but there remains a need for careful investigation of the properties of monolayer flakes as well as a deeper understanding of the process of degradation under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%